ANALYSIS OF BOTTLED DRINKING WATER (AMDK) BUSINESS STRATEGIES IN IMPROVING THE ECONOMY OF Islamic Boarding Schools (CASE STUDY OF MAMBAUL ULUM Islamic Boarding School, BATA-BATA PAMEKASAN) - Zolehah, Linda Imroatus; Rohman, Abdur (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
At this time, the business world is entering an era of globalization, where all parties can freely enter any desired market, both domestically and abroad, without any restrictions. Seeing these conditions, every business sector should be required to know and follow climate developments or changes in every business activity. The company must clearly determine the direction in which its business activities are carried out and which parties are the targets of the movement of its business activities or in other words, having determined the direction of its business activities, the company must determine which parties are the targets of the sales of the products offered by the company. Bottled Drinking Water (AMDK) as a newly growing industry has been encouraged to increase national economic growth in the last year. In terms of the number of companies operating in the AMDK sector, according to the Association of Indonesian Bottled Drinking Water Companies (Aspadin), it continues to increase. The increasingly rapid progress in AMDK has encouraged many companies in this industry to expand their production and markets, as well as encouraging the entry of new entrants. The situation that has developed in recent years is increasing competition. The aim of this research is to find out the business strategy for bottled drinking water to improve the economy of the Mambaul Ulum Bata-bata Islamic Boarding School Cooperative. The type of research used in the research is SWOT analysis. The sample used in this research was 30 respondents, namely employees at the Aneka Usaha Bata-bata Islamic Boarding School Cooperative (KOPPONTREN AUBA). Data collection techniques in this research used interviews and observation. Based on the results of business strategy analysis research conducted by KOPPONTREN AUBA to improve the economy of its Islamic boarding schools, KOPPONTREN AUBA implements five business strategies, namely the first SO (Strengths-Opportunities) strategy by expanding market share by carrying out effective and efficient promotions, expanding cooperation with various parties , the second is the ST (Strength - Threats) strategy by managing product quality and carrying out product innovation, the third is the WO (Weakness-Opportunities) strategy by increasing promotions both online and offline and increasing the effectiveness of promotions, the fourth is the WT (Weakness-Threaths) strategy by how to increase the promotion of Labini AMDK to the community. Keywords: Strategy, Business, AMDK, SWOT